Adolescent with Matricidal and Suicidal Thoughts a Case Report - Polat, Berna; Yıldırım, Veli; Toros, Fevziye (The Bulletin of Legal Medicine, 2015)
Matricide can be defined as the murder of mother by her son or daughter. The study conducted to investigate the relationship among biological, physiological and environmental affect on behavioural homicide such as matricide are seem rarely in literature and it is also hard defined acquired information about this issue. This case report was presented to contribute the literature about this kind of situation.
Keywords: adolescent; matricide; homicidal behaviours